Molecular characterization of vaginal microbiome of lactating dairy water buffaloes (Bubalus bubalis, Lin.) using polymerase chain reaction-denaturing gradient gel electrophoresis (PCR-DGGE) - Carpio, Joey Marvin C.; Nayga, Jehan F.; Tubalinal, Gabriel Alexis S. P.; Mingala, Claro N. (2022)
The study characterized the bacterial microbiome in the vagina of lactating dairy water buffaloes using denaturing gradient gel electrophoresis (DGGE) of the 16S rRNA gene. This research was conducted to serve as baseline study for future studies on vaginal microbiome and its possible effect on production and reproduction of dairy water buffaloes. Molecular characterization of 16S rRNA genes of the different band after DGGE revealed that 15 (46.87%), 15 (46.87%) and two (6.25%) of isolated microbiomes had 100%, 90-99% and below 89% sequence homology, respectively. Out of the 32 isolates sequenced, the top three most isolated bacteria were Comamonas sp., E. coli, and Acidovorax sp. with nine (28.13%), four (12.5%) and three (9.36%) isolates, respectively. The other bacteria isolated with two (6.25%) isolates each were Stenotrophomas maltophila, Klebsiella pneumoniae, Microbacterium sp., Pedobacter sp. and one (3.16%) each of Enterococcus faecium, Lysinibacillus capsici, Enterobacter, Variovorax, Flavobacterium, Alpha Proteobacterim and an Uncultured bacteria clone. This was the first study of characterization of the 16s rRNA gene of the vaginal microbiome of dairy water buffaloes in the Philippines using PCR-DGGE.
Keywords: Water buffalo; Electrophoresis; Microbiomes